Syuhada A`Lannas: Road Map Penanaman Sikap Patriotisme Melalui Nilai Islam Wasathiyah dalam Al-Qur’an - Zezen Zainul Ali; Annisa Wulandari (MODERATIO: Jurnal Moderasi Beragama, 2023)
This study will discuss the Road Map or guidelines in the effort to form an attitude of patriotism through the concept of Syuhada 'ala Nas as an implementation of Islam Wasathiyah values so that Syuhada 'ala Nas can be a reference in attitude and become an example that can be applied in the life of the nation and state. patriotic. This research is library research, the data used is taken from several kinds of literature in the form of books, and journals that have similarities in the object of study. So, it was found that efforts in constructing an attitude of patriotism have been conceptualized and taught in Islam, namely in the meaning of Syuhada 'ala Nas in Surah Al-Baqarah: 143, Syuhada 'ala Nas has the meaning of testimony, as a witness must have fair and moderate values. middle as contained in Islam Wasathiyah values. The relevance between Islam Wasathiyah and the value of Patriotism provides a road map for inculcating patriotism, namely through the meaning of Syuhada 'ala Nas.